2006 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--434
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis Of Graduation Rates At Research Universities

Abstract: is a Ph.D. Candidate in Industrial and Operations Engineering at the University of Michigan. She is a quality consultant and has an interest in applying Quality Engineering techniques to Engineering Education research. Her professional affiliations include ASEE, ASQ and INFORMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…It is Common knowledge that completion of studies within the stipulated time is the goal of every student. A study of large universities in the USA (Veenstra & Herrin, 2006) found out that private universities had higher completion rates than public universities. In Nigeria, Albar and Onye (2016) observe that completion rates in public universities were very low because of frequent lecturer strikes.…”
Section: Issn: 2663-9319mentioning
confidence: 99%
“…It is Common knowledge that completion of studies within the stipulated time is the goal of every student. A study of large universities in the USA (Veenstra & Herrin, 2006) found out that private universities had higher completion rates than public universities. In Nigeria, Albar and Onye (2016) observe that completion rates in public universities were very low because of frequent lecturer strikes.…”
Section: Issn: 2663-9319mentioning
confidence: 99%
“…As used in many large research universities, graduation rates are reported through 6-year graduation [2]. Also, TAMU engineering students are required to graduate with a "high-impact experience", which includes a global program or internship [3].…”
Section: B Graduation and Retention Ratesmentioning
confidence: 99%